Tenets of a holistic approach to drinking water-associated pathogen research, management, and communication. (1st March 2022) - Proctor, Caitlin; Garner, Emily; Hamilton, Kerry A.; Ashbolt, Nicholas J.; Caverly, Lindsay J.; Falkinham, Joseph O.; Haas, Charles N.; Prevost, Michele; Prevots, D Rebecca; Pruden, Amy; Raskin, Lutgarde; Stout, Janet; et al.
Highlights: Drinking water pathogen research often lacks cross-disciplinary communication. Differences in pathogen behavior and management should be considered holistically. Discipline-specific methods, vocabulary, and goals hinder cross-disciplinary work. Comprehensive messaging and research regarding these pathogens is recommended. Abstract: In recent years, drinking water-associated pathogens that can cause infections in immunocompromised or otherwise susceptible individuals (henceforth referred to as DWPI), sometimes referred to as opportunistic pathogens or opportunistic premise plumbing pathogens, have received considerable attention. DWPI research has largely been conducted by experts focusing on specific microorganisms or within silos of expertise. The resulting mitigation approaches optimized for a single microorganism may have unintended consequences and trade-offs for other DWPI or other interests (e.g., energy costs and conservation). For example, the ecological and epidemiological issues characteristic of Legionella pneumophila diverge from those relevant for Mycobacterium avium and other nontuberculous mycobacteria. Recent advances in understanding DWPI as part of a complex microbial ecosystem inhabiting drinking water systems continues to reveal additional challenges: namely, how can all microorganisms of concern be managed simultaneously? In order to protect public health, we must take a more holistic approach in all aspects of the field, including basic research, monitoring methods, risk-based mitigation techniques, and policy. A holistic approach will (i) target multiple microorganisms simultaneously, (ii) involve experts across several disciplines, and (iii) communicate results across disciplines and more broadly, proactively addressing source water-to-customer system management. Graphical abstract: Image, graphical abstract